Halal but Forbidden? A Systems Approach to Tompangan Transactions in Sumenep, Madura - Suaidi; Ali Sodiqin (El-Mashlahah, 2025)
The tompangan tradition in Sumenep, Madura, is a long-standing form of communal cooperation involving exchanging money and goods. However, on November 12, 2023, during a bahsul masā’il session, the Sumenep branch of Nahdlatul Ulama (PCNU), led by KH. Hafidzi Syarbini declared that the practice is “permissible but prohibited.” This ruling reflects growing public concerns over its negative effects, as tompangan has increasingly shifted from social solidarity toward profit-oriented practices that burden families economically. The study examined the transformation through the lens of maqāṣid al-syarī‘ah using Jasser Auda’s systemic approach. Employing a socio-legal, qualitative-exploratory method, data were collected through interviews and literature review. The findings reveal a shift in value from social to profit-driven orientations; many transactions have become individualistic, self-serving, and textually exclusive, neglecting broader ethical and social considerations. As the result, this shift fails to realize both the al-hadaf (immediate goals) and al-gayah (ultimate purposes) of Islamic law, diverging from Auda’s systemic interpretation of the maqāṣid. The study contributes by framing tompangan, not merely as a socio-cultural phenomenon but also as a legal-ethical case that illustrates the tension between ʿurf and the higher objectives of Islamic law. The findings enrich contemporary Islamic legal discourse by offering the systemic maqāṣid framework as a critical analytical tool for evaluating socio-religious practices.